1993
DOI: 10.1111/j.1365-2605.1993.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic alcoholism on semen—studies on lipid profiles

Abstract: The effect of chronic alcoholism on various seminal parameters (sperm concentration, rate of forward motility, percentage of abnormal spermatozoa, lipid profiles of seminal plasma and spermatozoa) was studied together with the serum levels of testosterone and oestradiol. In chronic alcoholics there was a marked reduction in sperm concentration and in the rate of their forward motility, and increase in the number of spermatozoa with morphological abnormalities when compared to age-matched normal fertile subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…It also has teratogenic effects on the foetus during pregnancy (Gordon et al, 1976;Oullette et al, 1977;VanThiel et al, 1980;Kumar, 1982). Human and animal studies have both shown that alcohol consumption produces significant spermatozoal morphological changes (VanThiel et al, 1980;Brzek, 1987;Gomathi et al., 1993) and reduced sperm quality has been reported in chronic alcoholics (VanThiel et al, 1980;Brzek, 1987;Gomathi et al, 1993). Testicular damage can occur (VanThiel et aL, 1975) and sperm motion characteristics such as progressive motiiity are reduced (Pajarinen etal., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It also has teratogenic effects on the foetus during pregnancy (Gordon et al, 1976;Oullette et al, 1977;VanThiel et al, 1980;Kumar, 1982). Human and animal studies have both shown that alcohol consumption produces significant spermatozoal morphological changes (VanThiel et al, 1980;Brzek, 1987;Gomathi et al., 1993) and reduced sperm quality has been reported in chronic alcoholics (VanThiel et al, 1980;Brzek, 1987;Gomathi et al, 1993). Testicular damage can occur (VanThiel et aL, 1975) and sperm motion characteristics such as progressive motiiity are reduced (Pajarinen etal., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of lipids in sperm, capacitation (13), alcoholism (14), storage (15), and passage through the epididymis (16) or cervical mucus (17) have been found to alter lipid composition. Although there are many studies on lipids in sperm, there has been no comprehensive, comparative study on the lipid composition of eggs versus sperm, or their changes during fertilization.…”
Section: Lipid Signaling Related To Fertilizationmentioning
confidence: 99%
“…CHRONIC male alcoholics and experimental animals exposed to ethanol have subnormal levels of testosterone [1][2][3][4][5]. The Leydig cells are the primary source of testicular androgen [6].…”
mentioning
confidence: 99%